I Congresso Mineiro de Educação(1983): uma história parcialmente contada - Nakamura, Tânia Maria Teixeira (2003)
This thesis has the objective of analysis on the Brazilian Educational History, using the Michel Foucalfs discourse analysis on academical works, official documentation and newspaper articles of the "I Congresso Mineiro de Educação", called as a historical "turning point" on brazilian education, by various authors, in the context of redemocratization process of the decade of 1980. We intent to understand the origin and the uses of that valorization do “1 Congresso Mineiro”, as a “monument”, “social artifact”, “social construction”, worked to fulfill the demand of a alternative political discourse, to the use of the rising social forces and the necessity of a “Original Act” to legitimate this group, their discourses and action. We will too work the role of press in the decade of 1980, their complex connections with the social, politic and economic momentum, their marks in the joumalistic discourse, specially in the context of the “I Congresso Mineiro de Educação”; the fragmentary knowledge, the omissions and value-driven selections in the construction of any discourse, the double meaning of “parti ality”, when using the joumalistic text as “font” or “document”.